The Case Against Leaders: A Moral Reading of Geir Haarde's Conviction for Negligence of Ministerial Duties - Ólafsson, Jón (Frontiers in Political Science, 2021)
In the aftermath of the Icelandic economic crisis of 2008 Iceland's former Prime Minister Geir Haarde was convicted for negligence of his constitutional duty to consult with his ministers on measures to prepare for the coming crisis. The court ruled that there was sufficient information available to the government to conclude that there was real danger of a major banking crisis in the months preceding the crisis. Mr. Haarde was the only head of government to be convicted in the aftermath of the Financial crisis. His indictment and conviction was hotly debated in Iceland where many people considered the process unfair, primarily because Mr. Haarde was the only minister indicted by Parliament for negligence of duties although a Special Investigative Commission appointed by Parliament had recommended indicting other ministers and officials as well. The paper reviews the case against Haarde and the public reaction to it. It is argued that the majority of judges on the special court which convicted Mr. Haarde used the constitutional clause on the duty to conduct ministerial meetings to present a more wideranging condemnation of Haarde's failure to deal with and acknowledge the threats Iceland was facing. Public opinion changed over time: When the Parliament began its consideration of whether to indict former ministers surveys showed an overwhelming majority favoring indictments, but limited confidence that anyone would actually be indicted. When proceedings against Mr. Haarde started public support was much less. After the conviction opinion polls have shown growing doubts about the special court itself. The whole case is an interesting example of the elusiveness of accountability: The paper argues that a thoroughgoing moral reading of Mr. Haarde's conviction reveals a more damning analysis og his actions (and lack of actions) than has generally been acknowledged by political leaders and in public debates.